Global, regional, and national trends in the incidence of pneumoconiosis among populations aged 20 and above from 1990 to 2021 - Cheng, Qiyun; He, Shiyue; Hu, Yongbin; Pan, Pinhua; Hu, Xinyue; Liao, Shuya; Wang, Shunjun; Li, Hui (Frontiers in Public Health, 2025)
BackgroundPneumoconiosis remains one of the most critical occupational health hazards globally. Utilizing data from the Global Burden of Disease (GBD) 2021, we have updated the epidemiological trends of pneumoconiosis.MethodsWe conducted and analyzed pneumoconiosis-related data from the GBD 2021 study for individuals aged ≥20 years. Our analysis described the incident cases and age-standardized incidence rates (ASIRs) across various global regions and age groups. Temporal trends were evaluated using Estimated Annual Percentage Change (EAPC) for ASIRs between 1990 and 2021.ResultsThe ASIR of pneumoconiosis among individuals aged ≥20 years declined globally at an annual average of 0.48% between 1990 and 2021. Except for high socio-demographic index (SDI) regions, the ASIR of pneumoconiosis declined across all other SDI categories. Males had significantly higher incidence rates than females, especially in older adults. Silicosis emerged as the predominant type of pneumoconiosis, constituting ~56.7% of cases. While the ASIRs for silicosis, coal workers' pneumoconiosis, and other pneumoconiosis decreased, the ASIRs for asbestosis exhibited a notable upward trend, with an EAPC of 1.21%. A strong negative correlation was observed between the EAPC of pneumoconiosis incidence and the 1990 ASIRs values. Notably, the EAPC showed a statistically significant but very weak positive correlation with the 2021 Human Development Index (HDI) values.ConclusionDespite a gradual global decline in the ASIR of pneumoconiosis, the disease burden remains substantial in certain regions. Our findings could inform governments and policymakers in developing targeted prevention strategies to mitigate this burden. Future strategies should integrate technological innovation with regulatory frameworks, prioritizing male-dominated high-risk sectors through strengthened global asbestos bans and lifetime health surveillance for workers in pneumoconiosis-prone occupations worldwide.